(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The design, analysis, and experimental validation of a high gain circularly polarized antenna array tailored for telemetry applications at the S-band frequency. Telemetry plays a pivotal role in various fields, including aerospace, remote sensing, and medical devices, where reliable data transmission is essential. The proposed antenna array aims to address the demands of telemetry systems operating in the S-band (2-4 GHz), offering enhanced communication performance. Through meticulous design and optimization, we achieve a high gain antenna array with circular polarization characteristics, making it suitable for both transmit and receive functions in telemetry applications. The research encompasses detailed electromagnetic simulations, experimental measurements, and comparisons, demonstrating the antenna array’s suitability and effectiveness. The results highlight the antenna’s potential to significantly improve telemetry communication in S-band applications, paving the way for enhanced data transmission and reception capabilities in diverse fields of science and technology.